An Assessment of the Influence of Reverse Logistics Practices on Solid Waste Disposal Management in Kisumu Town, Kenya - Oyier, Ingrid Loreta (JOOUST, 2021)
Reverse logistics is a process that involves the implementation, control, and planning of cost-effective flow of raw materials, finished goods, and in-process inventory. It is the flow from the point of consumption to the point of origin to ensure effective disposal and recapturing of value. Reverse logistics is a new practice in developing countries such as Kenya, and as such, there is need to fully understand what it entails. Based on this, the main purpose of the study is to assess the influence of reverse logistics practices on solid waste disposal management in Kisumu Town, Kenya. The study was guided by three main objectives which are to examine the influence of backward flow of materials on solid waste disposal management; to determine the influence of producers’ involvement on solid waste disposal management; and to establish value recovery opportunities in solid waste disposal management. The study utilized three theories which are Closed-loop supply chain theory (main theory), third-party logistics theory, and resource advantage theory. The study used descriptive survey design. Descriptive survey design was used. The target population of the study was 140 respondents consisting of representatives of supermarkets, garbage collecting organizations, employees of the county government, producers, and small-scale hotels. A stratified random sampling of 104 respondents was surveyed. Data was collected using questionnaires and interview guides. Quantitative data was analyzed using descriptive and inferential statistics, which includes measures of variability and central tendency. Qualitative data was analyzed using thematic analysis framework. Reliability was ensured using the Cronbach Alpha that had a value of 0.7. The validity of the instruments was determined by the supervisors of the institution. The findings of the study indicated that there has been a limited adoption of backward flow of materials as a reverse logistics practice, that producers are not fully involved in the implementation and practice of solid waste disposal management and that solid waste disposal management practices in Kisumu Town have not been fully used to exploit value recovery opportunities. The conclusion of the study was that there is need to increase the utilization of reverse logistics practices in Kisumu Town. Some of the recommendations that are provided in the study include the need to implement reverse logistics practices to reduce expenditures, increase profitability, improve efficiency, and promote environmental sustainability, there is need for collaboration of major stakeholders in solid waste disposal in providing training on waste handling and there is need in reducing garbage collection fees to ensure that it is affordable.
Keywords: Environmental sustainability; Waste disposal management